Pengaruh Promosi Media Sosial dan Harga Terhadap Minat Beli Konsumen (Survey Pada Pengikut Akun TikTok Kopi Kenangan) - Danisa Alsyafira S; Widyastuti Nurmalia Utami; Palupi Permata Rahmi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study was conducted to examine the level of social media promotion and price on the purchasing interest of Kopi Kenangan customers who follow the TikTok account. In this study, a quantitative approach was used with descriptive and verificative analysis. The purposive sampling process was applied to determine the sample; one hundred people surveyed were followers of the Kopi Kenangan account on TikTok. Data were analyzed using SPSS version 27 and obtained through the distribution of a Likert scale questionnaire. The analysis techniques used included validity and reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination, and hypothesis testing using t-tests and f-tests. Based on the analysis results, this study indicates that social media promotion and price have a positive and significant impact on consumer interest in purchasing products, onsidered independently and concurrently. Furthermore, these findings highlight the importance of digital marketing strategies on social media and appropriate pricing in increasing customer interest in Kopi Kenangan. Social media promotions have a stronger impact than price in increasing customer interest in the product. This study applied a non-probability sampling method in the sampling process.